The Future of Racial Memory:: Forgiveness, Reconciliation, and Redress in Joy Kogawa’s Obasan and Itsuka - McGonegal, Julie (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2005)
The majority of criticism surrounding Kogawa's Obasan and Itsuka assumes that reconciliation and resistance to racial injustice are incompatible, thereby overlooking Kogawa's complex exploration of the transformative potential forgiveness and reconciliation can provide Japanese Canadians in resisting and defusing the power of the oppressor. Forgiveness can only follow an apology that acknowledges wrongdoing; it does not merely reinscribe ideologically racist messages of power operating in Canadian society, nor invoke the "model minority myth" to avoid compensatory action. Such recognition of the past, however, is necessarily dependant on memory, which both texts represent as unstable and unreliable yet essential to the healing process. Kogawa contends with the tension between these postmodern and humanist concepts of memory through the issei word "Itsuka," meaning "someday," which captures the Japanese sense of the anteriority of the future. Forgiveness essentially constitutes a form of renarration that recollects the past while simultaneously opening up possibilities for a future.